2003
DOI: 10.1523/jneurosci.23-06-02131.2003
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle Regulators in the Neuronal Death Pathway of Amyotrophic Lateral Sclerosis Caused by Mutant Superoxide Dismutase 1

Abstract: There is growing evidence for involvement of members of the cyclin-dependent kinase (Cdk) family in neurodegenerative disorders and in apoptotic death of neurons subjected to various insults. After our recent report that a deregulation of Cdk5 activity by p25 may contribute to pathogenesis of amyotrophic lateral sclerosis (ALS), we further examined the possible involvement of other Cdks in mice expressing a mutant form of superoxide dismutase (SOD1 G37R ) linked to ALS. No substantial changes in Cdk2 or Cdk6 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
120
1
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(128 citation statements)
references
References 71 publications
3
120
1
4
Order By: Relevance
“…In vivo studies of cortical or spinal cord neurons after ischemia or excitotoxic-mediated DNA damage have shown the occurrence of apoptotic cell death associated with cyclin D1-cdk4, cyclin G, PCNA, or Rb͞E2F protein and mRNA overexpression (21)(22)(23)(24)(25). Inhibition of neuronal death, and improvement of functional recovery with flavopiridol treatment has been reported after brain ischemia in rats, although effects on glial and microglial cells were not addressed (39,40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo studies of cortical or spinal cord neurons after ischemia or excitotoxic-mediated DNA damage have shown the occurrence of apoptotic cell death associated with cyclin D1-cdk4, cyclin G, PCNA, or Rb͞E2F protein and mRNA overexpression (21)(22)(23)(24)(25). Inhibition of neuronal death, and improvement of functional recovery with flavopiridol treatment has been reported after brain ischemia in rats, although effects on glial and microglial cells were not addressed (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Cell cycle induction leading to apoptotic neuronal death has been described in vitro (15)(16)(17)(18)(19)(20) and in vivo, including animal models of stroke, amyotrophic lateral sclerosis, and Alzheimer's disease (12,(21)(22)(23)(24)(25). Although aberrant cell cycle activation can lead to apoptosis in postmitotic cells, cell cycle transition can also induce proliferation in mitotic cells such as astrocytes and microglia after brain ischemia (26,27).…”
mentioning
confidence: 99%
“…4.8 software, t nom is the nominal section thickness (of 30 mm in this study) and ssf is the fraction of the sections sampled or section sampling fraction (of 1/6 in this study). The volumes are reported as mm 3 . The subfield areas were delineated with a 2.5 Â objective lens.…”
Section: Methodsmentioning
confidence: 99%
“…1 In post-mitotic neurons, some pathological conditions upregulate cyclin D1/CDK4 complex expression to induce activation of E2F members that contributes to increased transcription of proapoptotic molecules. 2,3 However, it is unclear whether cyclin D1 expression directly induces neuronal death for a number of following reasons. First, due to a time lag between cyclin D1/CDK4 expression and the onset of DNA fragmentation, most cyclin D1-positive neurons show TUNEL negativity.…”
mentioning
confidence: 99%
“…In those studies, it was suggested that cell cycle signaling may affect the neuronal death pathway (25,33). Thus we hypothesized that the cell cycle might be affected by mutated Cu,Zn-SOD in FALS.…”
mentioning
confidence: 93%